Insulin resistance in heart failure: differences between patients with reduced and preserved left ventricular ejection fraction. (21st July 2015) - Scherbakov, Nadja; Bauer, Maximiliane; Sandek, Anja; Szabó, Tibor; Töpper, Agnieszka; Jankowska, Ewa A.; Springer, Jochen; von Haehling, Stephan; Anker, Stefan D.; Lainscak, Mitja; Engeli, Stefan; Düngen, Hans‐Dirk; et al.
Abstract : Aims: Insulin resistance (IR) is a characteristic feature of heart failure (HF) pathophysiology that affects symptoms and mortality. Differences in the pathophysiological profile of IR in HF with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF) are not characterized in detail. The aim of this study was to evaluate features of IR in HFpEF vs. HFrEF. Methods and results: We included 18 patients with HFrEF (EF 30 ± 11%, body mass index (BMI) 26.5 ± 3.3 kg/m 2 ), 22 HFpEF patients (EF 63 ± 7%, BMI 28.6 ± 4.8 kg/m 2 ), and 20 healthy controls of similar age, all without diabetes mellitus. Patients were in stable ambulatory condition and on stable medical regimens for HF. IR was assessed at fasting steady state by the homeostasis model assessment (HOMA) index and within the physiological range of insulin–glucose interactions by the short insulin sensitivity test (SIST). Fasting‐state IR was observed in HFpEF and in HFrEF in comparison with controls (HOMA 1.9, interquartile range (IQR) 1.5–3.6 vs. HOMA 3.1, IQR 1.4–3.7 vs. controls 1.2, IQR 1.8–0.9, respectively; analysis of variance P < 0.001), but no statistical difference was observed between HFpEF and HFrEF. The dynamic test over the physiological range of insulin–glucose interactions revealed a more severe IR in HFrEF as compared with HFpEF. Thus, glucose levels remained the highest in HFrEF (76 (64–89) mg/dL) at the end of the SIST compared with HFpEF and controls (68 (58–79) and 56 (44–66) mg/dL, respectively, P < 0.001). Conclusion: IR is present in non‐diabetic patients with HFpEF and HFrEF. However, distinct differences in the insulin sensitivity characteristics in HFpEF and HFrEF become apparent by more advanced testing. Patients with HFrEF showed more severe IR.